TRADITIONAL CRAFTS OF DAGESTAN IN THE CONTEXT OF HISTORICAL AND CULTURAL RELATIONS WITH THE REGIONS OF RUSSIA, COUNTRIES OF THE CAUCASUS AND THE MIDDLE EAST - Magomedov, Amirbek Dz.; Omarkadieva, Madina Abdurasidovna (History, Archeology and Ethnography of the Caucasus, 2022)
The present study examines the formation and mass development of artistic crafts in Dagestan for the past millennium. The evolution of traditional arts and crafts of Dagestan can be seen through the history of their formation, contacts of the inhabitants with foreign cultures. The leading approach in the study of the problem that combines historical-cultural, historical-comparative and artistic-descriptive methods, which allow for a comprehensive consideration of the cultural influences of neighboring (Transcaucasia, Russia) and the Middle Eastern countries on the development of arts and crafts in Dagestan over the past millennium. The article shows that the spread of Islam, close contacts of Dagestan with the peoples of Transcaucasia, Iran, the Middle East, the accession of Dagestan to Russia, foreign cultural influences of the Soviet era provided prerequisites for the development of professional and folk arts and crafts in Dagestan. At the same time, the craftsmen of Dagestan not only borrowed, but also redesigned many other cultural and ethnic traditions, creating new artistic forms and phenomena, often of a world and regional level. The historical development of Dagestan, associated with the spread of Islam, the influence of the Transcaucasian, Iranian, Middle Eastern, Russian-European, Soviet traditions of artistic culture, contributed to the formation in Dagestan of the traditions of religious architecture, ordinary, glazed and painted ceramics, carpet weaving, weapons, jewelry, coppersmithing, decorative stone and wood carvings, embroidery with gold and silk thread, etc. The provided material is of great scientific value for historians of culture and art, ethnographers, practitioners of arts and crafts and fine arts, for specialists engaged in educational practice in schools and universities.